Property rights and collective action for pro-poor watershed management - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Watersheds are simultaneously managed at various social and spatial scales, from microcatchments to transnational river systems and lake basins. They are also often managed for multiple objectives: environmental conservation and economic development. The flow of water, soil, nutrients, and other materials across a landscape extends the consequences of decisions about resource use well beyond the individual land user or manager, resulting in externalities. Upstream pollution by agricultural chemicals can expose downstream users to economic and health costs. More positively, upstream soil erosion can transport fertile soil that can enrich downstream rice paddies or other fields. Because watersheds have such broad impacts at so many levels, they have special implications for property rights and collective action in the management of resources.